Effect of Perianal Treatment with Baby Oil on Reducing the Degree of Diaper Dermatitis in Infants - Nour Sriyanah; Esse Puji Pawenrusi; Suradi Efendi; Harlina Harlina (GLOBAL HEALTH SCIENCE GROUP, 2022)
Diaper dermatitis is a skin problem in the perianal area. It is caused by skin contact with urine and feces in the diaper. Baby oil is considered to have a good treatment effect, especially with high levels of unsaturated fat as a protector, so that urine and dirt do not stick directly to the skin that causes irritation. This research method used a quasi-experimental. The population is all infants with diaper dermatitis in the working area of PUSKESMAS (Public Health Center) Bajeng, Gowa Regency, as many as 21 people. The examination was conducted by purposive sampling with 20 respondents. This research was conducted for 25 days using an observation sheet as a research instrument. Statistical test using Paired t-test, with the determined value of p = 0.000, simpler than = 0.05. The results showed that there was an effect of perianal treatment with baby oil on reducing the degree of diaper dermatitis in infants. From this research, it can be concluded that the occurrence of diaper dermatitis in infants is affected by skin contact with wet diapers, waste compounds, and the type of diaper used. Perianal treatment is carried out routinely using baby oil every post-defecation and urination for 6 days, making the infants' skin remain intact, dry, odorless, and produces residual protein so that it is not easily absorbed in the skin.